Comparison of Simple Modeling Approaches of the Nonlinear Magnetic Properties of a Single-Phase Transformer - Stupar, Jelena; Rahmanović, Ermin; Štumberger, Gorazd (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper analyses the potential of several analytic functions to describe the nonlinear magnetic properties of a single phase transformer’s iron core. A dynamic model of a single phase transformer with analytic functions describing magnetic properties was prepared in Simulink and used to calculate the inrush currents. The parameters of the chosen analytic functions were determined using differential evolution by minimizing the deviation between measured and calculated inrush currents in the time and frequency domains simultaneously. The ranking of the applied analytic functions based on the lowest deviation between measured and calculated currents is presented.